Spontaneous abdominal esophageal perforation in a patient with mitochondrial neurogastrointestinal encephalomyopathy. Issue 1 (February 2015) - Kalkan, I. H.; Köksal, A. Ş.; Evcimen, S.; Sapmaz, F.; Öztaş, E.; Önder, F. O.; Güliter, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is an autosomal recessive multisystem disorder caused by thymidine phosphorylase deficiency. Severe denutrition is almost constant during the course of the disease which leads to severe malnutrition and requires long-term parenteral nutrition in most cases. Patients with MNGIE syndrome and chronic intestinal pseudo-obstruction have a particularly poor prognosis and they usually die around 40 years of age. Gastrointestinal perforation associated with MNGIE is extremely rare. Herein we present our unique case with MNGIE associated abdominal esophageal perforation.